Genome-wide identification and integrated analysis of lncRNAs in rice backcross introgression lines (BC(2)F(12)) - Li, Mengdi (BMC Plant Biol, 2020)
BACKGROUND: Distant hybridization is an important way to create interspecific genetic variation and breed new varieties in rice. A lot of backcross introgression lines (BILs) had been constructed for the scientific issues in rice. However, studies on the critical regulatory factor lncRNA in cultivated rice, wild rice and their BIL progenies were poorly reported. RESULTS: Here, high-throughput RNA sequencing technology was used to explore the functional characteristics and differences of lncRNAs in O. sativa, O. longistaminata and their three BC(2)F(12) progenies. A total of 1254 lncRNAs were screened out, and the number of differentially expressed lncRNAs between progenies and O. sativa were significantly less than that between progenies and O. longistaminata. Some lncRNAs regulated more than one mRNA, and 89.5% of lncRNAs regulated the expression of target genes through cis-acting. A total of 78 lncRNAs and 271 mRNAs were targeted by 280 miRNAs, and 22 lncRNAs were predicted to be the precursor of 20 microRNAs. Some miRNAs were found to target their own potential precursor lncRNAs. Over 50% of lncRNAs showed parental expression level dominance (ELD) in all three progenies, and most lncRNAs showed ELD-O. sativa rather than ELD-O. longistaminata. Further analysis showed that lncRNAs might regulate the expression of plant hormone-related genes and the adaptability of O. sativa, O. longistaminata and their progenies. CONCLUSIONS: Taken together, the above results provided valuable clues for elucidating the functional features and expression differences of lncRNAs between O. sativa, O. longistaminata and their BIL progenies, and expanded our understanding about the biological functions of lncRNAs in rice.